2005
DOI: 10.1007/s11664-005-0126-1
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of 4H-SiC P-N junction diodes by selective-epitaxial growth using TaC as the mask

Abstract: Selective nitrogen doping of 4H-SiC by epitaxial growth using TaC as the hightemperature mask has been demonstrated. Nomarski optical microscopy and scanning electron microscopy (SEM) were used to characterize selective growth of SiC. In addition, 250-µm, square-shaped, p-n junction diodes by selective n-type epitaxial growth on a p-type epilayer were fabricated. The refilled fingers with different width were designed to vary the periphery/area (P/A) ratio. The effects of P/A ratio on the current-voltage (J-V)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…18 We also did this but discovered uneven formation of carbide surface and also the Ta reacted at with the SiC at 1600°C, as shown in Fig. For selective area growth of SiC, Ta mask has been formed by evaporating a Ta film onto the SiC substrate, patterning and etching it, and then carburizing it in a propane atmosphere.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…18 We also did this but discovered uneven formation of carbide surface and also the Ta reacted at with the SiC at 1600°C, as shown in Fig. For selective area growth of SiC, Ta mask has been formed by evaporating a Ta film onto the SiC substrate, patterning and etching it, and then carburizing it in a propane atmosphere.…”
mentioning
confidence: 95%
“…18 One interesting possibility is that TaC could grow epitaxially on the SiC making it possible to use for SAE at high temperatures. For this to be done, the areas where growth should not occur must be covered by a material for which it is difficult for SiC to nucleate and grow on.…”
mentioning
confidence: 99%
“…1. Different from the conventional vertical pn diodes [7], both electrodes of the 4H-SiC diodes were designed to be located on the top side of the chip to permit the integration of the four diodes. The top and cross-sectional views of the integrated 4H-SiC pn diode bridge rectifier layout are shown in Fig.…”
Section: Integrated 4h-sic Diode Bridge Rectifiermentioning
confidence: 99%
“…It is reported that SiC pn junctions formed by embedded epitaxy exhibit lower leakage current when the sidewalls are {1120} rather than {1100} [212]. Selective embedded epitaxy by using carbon [213] or TaC [214] as masking materials has also been reported. Figure 4.39 shows a cross-sectional TEM image of SiC trenches filled by embedded epitaxy [211].…”
Section: Embedded Homoepitaxy Of Sicmentioning
confidence: 99%